Comparison of giving behaviour in Western Australia - Shanka, Tekle; Oroz, Ivana (School of Marketing, Curtin Business School, 2009)
This paper presents the results of survey data examining the differences and similarities of giving behaviour between university students and members of the public in Western Australia (WA). The two groups reported donating behaviour and intended donating behaviour using an established scale from Sargeant, Ford and West (2006). A convenience sample of 400 members of the general public 287 higher education students participated in a survey to explore their motivations behind giving. The results indicate that female participants generally tend to be more positive towards giving to non-for-profit organisations. Trust, emotional utility and familial utility were significant predictors of commitment that leads to future giving behaviour.